Prosentase Penggunaan Amoksisilin secara Rasional untuk Swamedikasi Salesma - Rehana Rehana; Sri Sutji Susilawati; Iskandar Sobri (Fakultas Farmasi Universitas Pancasila, 2007)
The high frequency of common cold self medication using amoxycillin should be given serious attention, while the percentage of its use should be known. Investigation was carried out by a cross sectional survey study using questionaire as primary data (containing indication, dosage, and duration of therapy) in several pharmacies in Banyumas and Purbalingga during four months since December 2006 until March 2007. Investigation was carried out using 85 samples, 69 addult (81 %) and 16 children (19 %). Rational use of amoxycillin consisted of 61 samples (71,76 % ) and irrational use 24 samples (28,24 %). Irrational use of amoxycillin was caused by irrational indication, but 100% rational use were observed based on dosage and duration of therapy.